2014
DOI: 10.1371/journal.pone.0094385
|View full text |Cite|
|
Sign up to set email alerts
|

Shorter Men Live Longer: Association of Height with Longevity and FOXO3 Genotype in American Men of Japanese Ancestry

Abstract: ObjectivesTo determine the relation between height, FOXO3 genotype and age of death in humans.MethodsObservational study of 8,003 American men of Japanese ancestry from the Honolulu Heart Program/Honolulu-Asia Aging Study (HHP/HAAS), a genetically and culturally homogeneous cohort followed for over 40 years. A Cox regression model with age as the time scale, stratified by year of birth, was used to estimate the effect of baseline height on mortality during follow-up. An analysis of height and longevity-associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
67
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 40 publications
7
67
0
Order By: Relevance
“…Rather, it is that, " modern medicine and improved sanitation have sharply reduced infant, maternal and childhood mortality" (Samaras 2012, p. 248). A direct association study by He and colleagues (He et al, 2014) reports that shorter adult height is associated with greater longevity in both Japanese and American men.…”
Section: -----------------------------------------mentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, it is that, " modern medicine and improved sanitation have sharply reduced infant, maternal and childhood mortality" (Samaras 2012, p. 248). A direct association study by He and colleagues (He et al, 2014) reports that shorter adult height is associated with greater longevity in both Japanese and American men.…”
Section: -----------------------------------------mentioning
confidence: 99%
“…Rather, it is that, " modern medicine and improved sanitation have sharply reduced infant, maternal and childhood mortality" (Samaras 2012, p. 248). A direct association study by He and colleagues (He et al, 2014) reports that shorter adult height is associated with greater longevity in both Japanese and American men.Moreover, this association seems to be mediated by a single nucleotide polymorphism of the G allele of the FOXO3 SNP (Willcox et al, 2008) that may also directly reduce growth in height. Evidence for a similar height-longevity association for women is not known, but we note that Japanese women are, on average, one of the longest lived populations but not one of the tallest -they rank 90 th in the NCDRisC height database.…”
mentioning
confidence: 99%
“…Although a small part of this substantial difference could perhaps be attributable to body posture, the standardized assessment of height in standing position suggests that the observed difference is real. Height may be inversely associated with longevity (He et al 2014), but a differential mortality before age 60 years would be unlikely to generate a difference in height as large as the one observed. A previous study from this mass arsenic poisoning already reported lower height among exposed victims at adolescence, although details were not provided (Uehata et al 1977).…”
Section: Discussionmentioning
confidence: 99%
“…About 25 distinct biological factors have been identified (11,13,14,16,19) that support the benefits of smaller human body size in terms of health and longevity. For example, when compared to taller people of the same body proportions, shorter people have lower blood pressure, lower left ventricular mass, lower DNA damage, lower C-reactive protein, and lower insulin and insulin like growth factor-1.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, a large study (16) tracked about 8000 elderly male Japanese Hawaiians for over 40 years. The researchers found that shorter men lived longer, They also had lower insulin secretion, which is related to greater longevity (11).…”
Section: Taller Height/larger Body Sizementioning
confidence: 99%